Evolutionary Data Mining Design to Visualize the Examination Timetabling Data at a University: A First Round Development. - Thomas, J. Joshua; Khader, Ahmad Tajudin (2007)
Examination scheduling ("timetabling") at a University is a determined challenge. Allocating exam stipulate “time slots" requires most advanced quantitative techniques. This study takes an alternate approach of applying the principles of data mining (DM) explicitly using undirected data mining, data preprocessing to get the patterns in data then understand the relationship between them.